1976
DOI: 10.21273/jashs.101.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Placement of Phosphorus Fertilizer and Lime upon Growth of ‘Delicious’ and ‘Golden Delicious’ Apple Trees1

Abstract: Surface applications of dolomitic limestone raised the pH from 4.3 to 6.2 with diminishing effect to 15 cm. Although the pH was affected to 15 cm the available Ca was raised only to a depth of 7.5 cm. When the lime was applied in discrete zones as subsurface applications, the pH was raised to 6.1 and maintained at 5.8 to a depth of 30 cm. When lime and superphosphate were applied on the surface the distribution of Ca and P with depth was improved. Concentrations of Ca and P in leaf tissue of ‘Delicious’ and ‘G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For many decades, N fertilizer has been the primary nutrient element recommended for apple production in Washington (1). Although a response of apple trees to P is reported to be rare in commercial orchards (3,4), recent investigations have shown a marked response to soil-applied P by young apple trees grown in low-P soils in the Pacific Northwest (7,8) and in other areas (10)(11)(12). Koch et al (5) reported a response of apple seedlings to incorporations of P into fumigated soil with or without inoculations of mycorrhizae.…”
mentioning
confidence: 99%
“…For many decades, N fertilizer has been the primary nutrient element recommended for apple production in Washington (1). Although a response of apple trees to P is reported to be rare in commercial orchards (3,4), recent investigations have shown a marked response to soil-applied P by young apple trees grown in low-P soils in the Pacific Northwest (7,8) and in other areas (10)(11)(12). Koch et al (5) reported a response of apple seedlings to incorporations of P into fumigated soil with or without inoculations of mycorrhizae.…”
mentioning
confidence: 99%